Pengaruh Penerapan Model Pembelajaran Problem Based Learning Terhadap Kemampuan Literasi Sains Siswa SMPIT Cordova Samarinda - Nurseptiani, Syifa; Zulkarnaen, Zulkarnaen; Qadar, Riskan (JURNAL PEMBELAJARAN FISIKA, 2023)
Scientific literacy refers to an individual's ability to apply understanding of concepts, scientific processes, and the use of scientific knowledge to solve real-life problems. This research aims to the influence of the Problem Based Learning (PBL) learning model on students' scientific literacy abilities at SMPIT Cordova Samarinda with a focus on the subject of climate change. In addition, this research aims to measure improvements in indicators of scientific literacy skills among students. This research uses a quantitative approach with a quasi-experimental research type and a nonequivalent control group design. The research population consisted of class VII students at SMPIT Cordova Samarinda, totaling 140 students spread across five classes. The experimental group consisting of 30 Class VII B1 students and the control group consisting of 28 Class VII B2 students were selected as samples. Data collection involved an assessment consisting of 8 essay questions given to students before and after participating in the PBL session. This research shows a statistically significant positive effect of using the PBL model on students' scientific literacy skills, with the highest increase in indicators seen in evaluating and designing scientific investigations.